2005
DOI: 10.1021/pr049791k
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Characterization of A Triton-Insoluble Fraction from Chloroplasts Defines A Novel Group of Proteins Associated with Macromolecular Structures

Abstract: Proteomic analysis of a Triton X-100 insoluble, 30 000 × g pellet from purified pea chloroplasts resulted in the identification of 179 nonredundant proteins. This chloroplast fraction was mostly depleted of chloroplast membranes since only 23% and 9% of the identified proteins were also observed in envelope and thylakoid membranes, respectively. One of the most abundant proteins in this fraction was sulfite reductase, a dual function protein previously shown to act as a plastid DNA condensing protein.Approxima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 66 publications
3
42
0
Order By: Relevance
“…Very bright GFP fluorescence perfectly overlapped with the autofluorescence of the chlorophyll ( Figure 3A), demonstrating the chloroplast localization of HCF145. In agreement with the previous data suggesting nucleoid localization of HCF145 (Phinney and Thelen, 2005), we also observed spots of GFP signal within the chloroplast. Even when the fluorescence microscope settings were set on the highest sensitivity, not even traces of GFP fluorescence were detected anywhere else within the cell, demonstrating that HCF145 is very likely exclusively localized in the chloroplast ( Figure 3A).…”
Section: Hcf145 Is a Chloroplast Protein And Has A Modular Compositionsupporting
confidence: 93%
See 1 more Smart Citation
“…Very bright GFP fluorescence perfectly overlapped with the autofluorescence of the chlorophyll ( Figure 3A), demonstrating the chloroplast localization of HCF145. In agreement with the previous data suggesting nucleoid localization of HCF145 (Phinney and Thelen, 2005), we also observed spots of GFP signal within the chloroplast. Even when the fluorescence microscope settings were set on the highest sensitivity, not even traces of GFP fluorescence were detected anywhere else within the cell, demonstrating that HCF145 is very likely exclusively localized in the chloroplast ( Figure 3A).…”
Section: Hcf145 Is a Chloroplast Protein And Has A Modular Compositionsupporting
confidence: 93%
“…In a large-scale proteome approach, peptides of HCF145 were found in triton-insoluble fractions, representing the nucleoid fraction of the chloroplast (Phinney and Thelen, 2005).…”
Section: Hcf145 Is a Chloroplast Protein And Has A Modular Compositionmentioning
confidence: 99%
“…In the TAC proteome analysis described by Pfalz et al (2006) a PPR protein with a molecular weight of 97 kDa (pTAC2) was identified. Interestingly, Phinney and Thelen (2005) identified a pea protein of similar size in their nucleoid analysis which matched the monoisotopic masses of the same PPR protein, corroborating its presence in chloroplast nucleoids. In a recent analysis of spinach TAC, two further PPR proteins of 98 and 67 kDa were identified (Melonek et al 2012).…”
Section: Post-transcriptional Levels Of Gene Expressionmentioning
confidence: 62%
“…The TAC fraction is prepared from plastid membranes by release of the nucleoids with detergents and by subsequent purification involving sepharose gel filtration and other steps (Krause and Krupinska 2000;Pfalz et al 2006). Recent proteomic analyses of these (Pfalz et al 2006;Melonek et al 2012) and other nucleoid-enriched fractions (Phinney and Thelen 2005;Majeran et al 2012) have revealed that several of the newly identified DNA binding proteins were not inherited from the prokaryotic ancestors. Plastid proteins homologous to the abundant prokaryotic HU protein, on the other hand, were not detected in higher plants which stands in contrast to their identification in some algal plastids (Karcher et al 2009), in the apicoplasts of apicomplexans (Sato et al 2003) as well as in some dinoflagellates (Chan et al 2006).…”
Section: Analysis Of the Protein Composition Of Plastid Nucleoidsmentioning
confidence: 99%
See 1 more Smart Citation